Effects and Mechanisms of Cutting Upper Thoracic Sympathetic Trunk on Ventricular Rate in Ambulatory Canines with Persistent Atrial Fibrillation - Jie Cai; Min Tang; Hao Liu; Shiao Ding; Rongxin Lu; Wei Wang; Nan Ma; Ju Mei; Zhaolei Jiang (Cardiology Research and Practice)
Objective. The purpose is to observe the effects and neural mechanism of cutting upper thoracic sympathetic trunk (TST) on the ventricular rate (VR) during persistent atrial fibrillation (AF). Methods. Twelve beagle dogs were halving to the control group and experimental group, 6 dogs for each group. Both groups were performed with left atrial rapid pacing (600 beats/min) to induce sustained AF. The experimental group underwent cutting upper TST  after a sustained AF model was established, while the control group received thoracotomy without cutting TST. Bilateral stellate ganglion (SG) and left atrial myocardium were harvested for tyrosine-hydroxylase (TH) immunohistochemical staining. Results. After cutting upper TST for 30 minutes, the average VR was 121.5 ± 8.7 bpm (95% CI, 114.8 to 128.0) in the experimental group, which was significantly slower than that of the control group (144.5 ± 4.2 bpm (95% CI, 141.5 to 148.0)) (P<0.001). After cutting upper TST for 1 month, the average VR of the experimental group (106.5 ± 4.9 bpm (95% CI, 102.0 to 110.0)) was also significantly slower versus that of the control group (139.2 ± 5.6 bpm (95% CI, 135.0 to 143.8)) (P<0.001). Compared with the control group, both left stellate ganglion (LSG) and right stellate ganglion (RSG) of the experimental group caused neural remodeling characterized by decreased ganglionic cell density and reduced TH staining. TH-positive component was significantly decreased in the left atrium of the experimental group compared with the control group. Conclusions. Cutting upper TST could reduce fast VR during persistent AF. Cutting upper TST induced bilateral SG neural remodeling and reduced sympathetic nerve density in the left atrium, which could contribute to the underlying mechanism of VR control during AF.